Hepatic Transcriptome Analysis Provides New Insight into the Lipid-Reducing Effect of Dietary Taurine in High–Fat Fed Groupers (Epinephelus coioides) - Mingfan Chen; Fakai Bai; Tao Song; Xingjian Niu; Xuexi Wang; Kun Wang; Jidan Ye (Metabolites, 2022)
A transcriptome analysis was conducted to provide the first detailed overview of dietary taurine intervention on liver lipid accumulation caused by high–fat in groupers. After an eight-week feeding, the fish fed 15% fat diet (High–fat diet) had higher liver lipid contents vs. fish fed 10% fat diet (Control diet). 15% fat diet with 1% taurine (Taurine diet) improved weight gain and feed utilization, and decreased hepatosomatic index and liver lipid contents vs. the High–fat diet. In the comparison of the Control vs. High–fat groups, a total of 160 differentially expressed genes (DEGs) were identified, of which up- and down-regulated genes were 72 and 88, respectively. There were 49 identified DEGs with 26 and 23 of up- and down-regulated in the comparison to High–fat vs. Taurine. Several key genes, such as cysteine dioxygenase (CDO1), ADP–ribosylation factor 1/2 (ARF1_2), sodium/potassium–transporting ATPase subunit alpha (ATP1A), carnitine/acylcarnitine translocase (CACT), and calcium/calmodulin–dependent protein kinase II (CAMK) were obtained by enrichment for the above DEGs. These genes were enriched in taurine and hypotaurine metabolism, bile secretion, insulin secretion, phospholipase D signaling pathway, and thermogenesis pathways, respectively. The present study will also provide a new insight into the nutritional physiological function of taurine in farmed fish.